(untitled) - Ernst, Dieter (Paris, 1989)
Telling us a challenge for newly industrializing economies
Keywords: Technological innovations,Đổi mới công nghệ,Competition, International,Cạnh tranh, toàn cầu; Economic aspects,Khía cạnh kinh tế; Developing countries,Quốc gia đang phát triển